2019
DOI: 10.1016/j.ijppaw.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Trichinella spp. infection in bank voles (Myodes glareolus) – A long term study

Abstract: Rodents play an important role as reservoir hosts of zoonotic diseases. As a component of our long-term programme of monitoring parasitic infections in bank vole populations in three ecologically similar sites in NE Poland, we screened blood samples for signs of a serological response to the presence of Trichinella spp. The overall seroprevalence of Trichinella spp. was 1.52%, but prevalence was largely concentrated in one of our three study sites and confined to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
1
4
1
Order By: Relevance
“…antibodies. Our previous studies have reported differences in seroprevalence and prevalence between males and females in other rodent-borne parasites 27,72,73 , but here no consistent difference between the sexes was detected. While seroprevalence appeared to be female biased in a model that included bank voles and the grassland species (the latter as one taxon), this arose mainly because all five infected bank voles were female and there was a trend for female bias among M. arvalis and M. agrestis.…”
Section: Discussioncontrasting
confidence: 77%
“…antibodies. Our previous studies have reported differences in seroprevalence and prevalence between males and females in other rodent-borne parasites 27,72,73 , but here no consistent difference between the sexes was detected. While seroprevalence appeared to be female biased in a model that included bank voles and the grassland species (the latter as one taxon), this arose mainly because all five infected bank voles were female and there was a trend for female bias among M. arvalis and M. agrestis.…”
Section: Discussioncontrasting
confidence: 77%
“…Among these, both extrinsic factors (e.g., geographic location) and intrinsic factors (e.g., host sex) are known to play varying but crucial roles in exposure of hosts, and their susceptibility, to infection [1][2][3]. Analyzing pathogen dynamics in their wildlife reservoirs is essential in providing a good understanding of their epidemiology and facilitating informed decisions on appropriate measures for their control [4][5][6]. Wild rodents pose a particular threat for human communities because they constitute the most abundant and diversified group of all living mammals [7] and often adopt a synanthropic existence.…”
Section: Introductionmentioning
confidence: 99%
“…Biomonitoring is one of the most effective methods of predicting and preventing possible epidemics [ 33 , 41 , 42 , 43 , 44 ]. Searching for novel hosts or reservoirs of zoonotic pathogens should be a priority for public health and wildlife management institutions [ 32 , 45 ]. The introduction of SARS-CoV-2 to wildlife has caused the establishment of animal reservoirs (i.e., white-tail deer).…”
Section: Discussionmentioning
confidence: 99%